A method for treating waste lithium-ion batteries
Through the oxygen-free vacuum infrared carbonization and rotary extrusion separation technology, combined with magnetic separation, gravity separation and color separation, the problems of low purity and secondary pollution of waste lithium-ion batteries are solved, and efficient and environmentally friendly battery recycling is achieved. Effect.
Patent Information
- Application Number
- CN202411525223.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The existing waste lithium-ion battery recycling technology has problems such as low recycling purity, low recycling rate and possible secondary pollution.
Use oxygen-free vacuum infrared carbonization to treat waste lithium-ion batteries, and then separate positive and negative electrode materials through rotary extrusion equipment, and combine magnetic separation, gravity sorting and color sorting technologies to gradually separate valuable groups such as copper and aluminum. and improve its purity and recovery rate through screening and roll granulation.
It realizes efficient sorting and recycling of valuable components such as positive and negative electrode powder, shell and copper-aluminum in waste lithium-ion batteries, with high recovery and purity and no secondary pollution.
Smart Images

Figure CN119035230B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery recycling and processing, and in particular to a method for processing waste lithium-ion batteries. Background Art
[0002] With the rapid development of science and technology, lithium-ion batteries, as an important component of new energy, have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage systems. However, with the increase in usage, the treatment and recycling of waste lithium-ion batteries have become increasingly prominent. If waste lithium-ion batteries are not properly handled, they will cause serious pollution to the environment. At the same time, the valuable metal elements contained in the battery, such as copper, aluminum, cobalt, and manganese, have a high recycling value. The recycling of these metals can not only save resources, but also reduce the development of new ores and reduce environmental pressure. Therefore, the recycling technology of waste lithium-ion batteries has become a current research hotspot.
[0003] At present, the recycling technologies of waste lithium-ion batteries mainly include physical methods, chemical methods and biological methods. The physical method separates materials through mechanical crushing, screening and other means; the chemical method separates valuable metals through chemical reaction processes such as acid-base dissolution and extraction; the biological method uses microbial metabolic processes to leach metals. Among them, the chemical method is prone to cause secondary pollution to the environment; the biological method has a long treatment cycle and high treatment cost. The physical method is the mainstream method at present because of its low cost and no secondary pollution to the environment. However, the recovery purity of the physical method is low, and the recovery rate is low due to mechanical entrainment. Therefore, it is necessary to develop an efficient, low-cost and environmentally friendly method for the recycling and reuse of waste lithium-ion batteries to improve the recovery rate and recovery purity of metal materials in the battery. Summary of the invention
[0004] In view of the above problems existing in the existing methods for recycling waste lithium-ion batteries, the present invention provides a method for treating waste lithium-ion batteries, which realizes the efficient sorting and recovery of valuable components such as positive and negative electrode powders, shells, copper and aluminum in waste lithium-ion batteries. Not only is the processing cost low, but the recovery rate and purity of copper and aluminum are also high, and no secondary pollution is generated, which has high practical value.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] A method for treating waste lithium-ion batteries comprises the following steps:
[0007] Step a, discharging the waste lithium-ion batteries and then shredding them to obtain battery fragments;
[0008] Step b, carbonizing the battery fragments by infrared heating under oxygen-free vacuum conditions to obtain carbonized battery fragments;
[0009] Step c, placing the carbonized battery fragments in a stripping device provided with a rotary extrusion structure for stripping, and screening the obtained material through a first sieve to obtain a positive and negative electrode mixed powder and a primary sieve residue;
[0010] Step d, the first-level sieve residue is subjected to air flow pulverization and then sieved through a second sieve to obtain positive and negative electrode mixed powder and a second-level sieve residue; the second-level sieve residue is subjected to magnetic separation, gravity separation and color separation in sequence to obtain magnetic material, copper particles, aluminum particles and light materials respectively; the light materials are roller-granulated and then subjected to three-level screening to obtain positive and negative electrode mixed powder and copper-aluminum mixed powder; the copper-aluminum mixed powder is roller-granulated to obtain a copper-aluminum particle mixture;
[0011] Step e, subjecting the copper-aluminum particle mixture to four-stage screening to remove organic matter in the copper-aluminum particle mixture, then screening the copper-aluminum particle mixture from which the organic matter has been removed through a third sieve, collecting the material under the sieve, and screening the material under the sieve through a fourth sieve and a fifth sieve in sequence to obtain a copper-aluminum particle mixture with three particle size specifications;
[0012] Among them, the mesh number of the fifth sieve is greater than the fourth sieve and greater than the third sieve, the mesh number of the third sieve is 50-80 meshes, the mesh number of the fourth sieve is 60-100 meshes, and the mesh number of the fifth sieve is 80-200 meshes;
[0013] Step f, transporting the copper and aluminum particle mixtures of different particle sizes to the copper and aluminum separation system for separation to obtain copper particles and aluminum particles.
[0014] Compared with the prior art, the method for treating waste lithium-ion batteries provided by the present invention directly shreds the waste lithium-ion batteries after discharge, and performs infrared radiation heating on the shredded battery fragments under oxygen-free vacuum conditions, which can achieve rapid decomposition of the binder and the electrolyte, significantly reduce the reaction between the electrolyte and the electrode material at high temperature, avoid the loss of positive and negative electrode materials, ensure the quality of the recovered positive and negative electrode materials, and at the same time, avoid oxidation of the current collector under high temperature conditions; then the carbonized battery is peeled off through a rotary extrusion device, so that the positive and negative electrode materials are effectively separated from the current collector, and the current collector is minimized from being broken into small pieces and entering the positive and negative electrode materials, which is beneficial to improving the recovery rate of the current collector , and reduce the difficulty of subsequent separation; the remaining materials from which most of the positive and negative electrode materials have been removed are subjected to magnetic separation, gravity separation and color separation to obtain most of the copper powder and aluminum powder. There is also some unseparated copper-aluminum mixed powder in the remaining materials, as well as a small part of the positive and negative electrode materials and organic matter. The remaining materials are roller-granulated, and the copper and aluminum powders form copper particles and aluminum particles, while a small part of the organic matter and the positive and negative electrode materials are still in the form of powder. Subsequently, the organic matter and the positive and negative electrode materials are removed respectively by screening through a sieve with a specific aperture, and finally the high-purity copper-aluminum particle mixture obtained by screening is subjected to particle size classification, and the copper-aluminum particle mixtures with different particle sizes are sorted to obtain high-purity aluminum particles and copper particles.
[0015] The present invention obtains most of the copper powder and aluminum powder through oxygen-free vacuum infrared carbonization, extrusion stripping of the positive and negative electrode materials on the current collector, and combines magnetic separation, gravity separation and color separation. The remaining materials are screened and rolled, granulated, and graded according to the particle size, and different sorting is performed according to the particle size classification to obtain high-purity copper powder and aluminum powder. The recovered copper powder and aluminum powder have high purity and recovery rate, and the efficient sorting and recovery of valuable components are achieved without generating secondary pollution. This is not only beneficial to reducing the impact of waste batteries on the environment, but also can create economic benefits by recovering valuable materials, and has high practical value.
[0016] Furthermore, in step a, the waste lithium-ion battery is discharged in a salt solution with a mass concentration of 1% to 20%.
[0017] Exemplarily, the salt solution is one or more of a sodium chloride solution, a potassium chloride solution, a magnesium chloride solution, a sodium sulfate solution or a potassium sulfate solution.
[0018] Furthermore, in step a, the particle size of the battery fragments is 20 mm to 150 mm.
[0019] Furthermore, in step b, the temperature of the infrared heating carbonization is 400°C to 600°C, the heating rate is 100°C / min to 300°C / min, the insulation time is 3min to 15min, and the infrared wavelength is 0.75μm to 1000μm.
[0020] By using infrared radiation heating, the decomposition temperature of the binder and the electrolyte can be quickly reached, significantly reducing the decomposition time of the binder and the electrolyte, thereby avoiding the reaction of the electrolyte with the positive and negative electrode materials at high temperature, avoiding the loss of positive and negative electrode materials or the impact on the activity of the positive and negative electrode materials. At the same time, the copper and aluminum current collectors will not be oxidized in a vacuum oxygen-free atmosphere, which is beneficial to ensure the quality of the recycled copper and aluminum current collectors.
[0021] Furthermore, in step c, the stripping device is a hammer crusher.
[0022] Furthermore, in step c, the frequency of the stripping device is 35 Hz to 45 Hz, and the output particle size is 10 mm to 20 mm.
[0023] A hammer crusher is used to separate the positive and negative electrode materials from the current collector, and the positive and negative electrode materials are peeled off by hitting and squeezing. This can not only effectively ensure the de-powdering of the current collector, but also prevent the current collector from being broken into small pieces and entering the positive and negative electrode materials. This not only ensures the purity of the positive and negative electrode materials, but also helps to improve the recovery rate of the current collector.
[0024] It should be noted that some battery shell powder will be mixed into the positive and negative electrode materials in the hammer crusher. In order to improve the purity of the recovered positive and negative electrode materials, the positive and negative electrode mixed powder obtained by screening in step c can be separated from the positive and negative electrode materials by a demagnetizer.
[0025] Furthermore, in step d, the particle size of the material after air flow crushing is 1 mm to 10 mm.
[0026] Furthermore, in step d, the second screen is a drum screen, and the mesh size of the drum screen is 140 to 200 meshes.
[0027] There is still a small amount of positive and negative electrode materials in the primary sieve residue. The small amount of positive and negative electrode materials mixed therein are screened and separated again through the second sieve to improve the purity of the recycled fluid and the recovery rate of the positive and negative electrode materials.
[0028] Furthermore, in step d, the three-stage screening specifically comprises the following steps: screening the material after roller granulation through linear sieves with mesh numbers of 10-30 mesh and 140-200 mesh in turn, collecting on the 10-30 mesh linear sieve to obtain copper-aluminum mixed powder, and collecting under the 140-200 mesh linear sieve to obtain positive and negative electrode mixed powder;
[0029] The material on the 140-200 mesh sieve is sieved through a 140-200 mesh disc sieve, and the copper-aluminum mixed powder is collected on the sieve, and the positive and negative electrode mixed powder is collected under the sieve;
[0030] The copper-aluminum mixed powders are combined and granulated by roller pressing to obtain a copper-aluminum particle mixture.
[0031] In the three-level screening, what is collected on the 10-30 mesh linear sieve is a high-content copper-aluminum mixed powder (containing a small amount of positive and negative electrode materials and organic matter), what is collected under the 140-200 mesh sieve is the residual positive and negative electrode materials, and what is collected on the 140-200 mesh sieve is most of the copper-aluminum mixed powder and a very small amount of positive and negative electrode materials. In order to further remove the positive and negative electrode mixed powder, the material is screened with a 140-200 mesh disc sieve, and the copper-aluminum mixed powder on the 10-30 mesh linear sieve and the 140-200 mesh disc sieve are combined, and granulated by roller to form copper-aluminum powder to form copper-aluminum particles, while organic matter is mixed with copper-aluminum particles in the form of large flakes and positive and negative electrode materials in the form of powder. This mixing form is conducive to subsequent separation and improves the removal rate of organic matter and positive and negative electrode materials.
[0032] Furthermore, in step d, the particle size of the copper-aluminum particle mixture is 0.2 mm to 0.8 mm, and the bulk density is ≥ 3.8 g / cm 3 , the proportion of spherical particles is ≥80%.
[0033] Furthermore, in step e, the four-stage screening comprises the following steps: screening the copper particle mixture through a 14-40 mesh disc sieve, and collecting organic matter on a 14-40 mesh sieve.
[0034] The main purpose of the four-stage screening is to ensure that the hard-to-crush organic matter and copper-aluminum mixture can be separated when the carbonization process is poor.
[0035] Furthermore, step e also includes: collecting the copper-aluminum particle mixture with qualified particle size under a 50-80 mesh sieve; returning the copper-aluminum particle mixture on the 50-80 mesh sieve to step d to mix with the lightweight material for roller granulation and continue with subsequent steps.
[0036] The materials whose particle size does not meet the requirement of 50-80 mesh are returned in step d and roller granulated for recycling treatment until the particle size meets the requirement of 50-80 mesh. This recycling treatment method can ensure that there are no samples that need to be processed again in the production line, which greatly improves the purity and recovery rate of the current collector and the positive and negative electrode materials.
[0037] Furthermore, in step f, the air volume and vibration frequency are set according to the particle size of the copper-aluminum particle mixture, wherein the particle size of the copper-aluminum particle mixture is 60-100 mesh sieve, the fan frequency is 10Hz-35Hz, and the vibration frequency is 41Hz-48Hz; the particle size of the copper-aluminum mixture is 80-200 mesh sieve, the fan frequency is 10Hz-35Hz, and the vibration frequency is 35Hz-40Hz; the particle size of the copper-aluminum mixture is 80-200 mesh sieve, the fan frequency is 10Hz-35Hz, and the vibration frequency is 31Hz-35Hz.
[0038] If the particle sizes of copper and aluminum particles are greatly different, it is difficult to make copper and aluminum have obvious specific gravity differences, resulting in low purity of the recovered copper and aluminum. The present invention classifies the copper and aluminum particle mixture by particle size, which can ensure that copper and aluminum have a large specific gravity difference when the particle sizes are relatively consistent. Different sorting processes are selected for copper and aluminum mixtures with different particle size classifications, which can improve the sorting efficiency and the separation degree of copper and aluminum, thereby improving the purity of the recovered copper powder and aluminum powder.
[0039] It should be noted that in order to further improve the purity of the separated materials in each step, a pipeline demagnetizer is provided at the outlet of each material to remove the battery shell powder in the material and ensure the quality of the products at each outlet.
[0040] The method for treating waste lithium-ion batteries provided by the present invention realizes efficient recovery of valuable components such as positive and negative electrode powders, shells, copper and aluminum in waste lithium-ion batteries, and can perform pollution-free treatment of priceless components such as binders and plastic diaphragms without generating secondary pollution. Meanwhile, the recovery rate of recovered copper and aluminum can reach more than 99.5%, and the recovery rate of positive and negative electrode materials can reach more than 99.7%. The aluminum content in copper powder is 0.1%-0.3%, and the copper content in aluminum powder is 0.2%-0.4%. The purity of copper powder and aluminum powder is relatively high. In addition, the recovered positive and negative electrode materials, copper powder and aluminum powder do not need secondary processing and can be directly sold as products, thus having high promotion and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a process flow chart of the method for treating waste lithium-ion batteries in Example 1. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0043] Example 1
[0044] A method for processing waste lithium-ion batteries:
[0045] Step a, placing the waste lithium-ion battery into a NaCl solution with a mass concentration of 10% for discharge, so that the battery is in a power-free state;
[0046] Step b, the discharged battery is sent to the shredder through the feeder, the battery is broken into small pieces with a particle size of 80 mm, and then the battery pieces are transported to the infrared tunnel kiln through the pipeline conveyor, the infrared wavelength is adjusted to 0.8 μm, the temperature is increased to 500°C at a rate of 280°C / min, and the temperature is kept for 8 minutes to carbonize the binder, electrolyte, diaphragm and other organic matter;
[0047] Step c, conveying the carbonized material to a hammer crusher, the motor frequency is 40 Hz, the discharge particle size is 15 mm, and then conveying the material at the discharge port to a disc screen 1 with a mesh number of 120, the disc screen 1 has a diameter of 1.8 m, and the vibration frequency is 35 Hz, and vibrating screening is performed, and most of the positive and negative electrode materials are collected under the sieve, and the magnetic material (battery shell powder) is screened out through a pipeline demagnetizer; most of the copper-aluminum mixed powder and a small amount of organic matter, positive and negative electrode materials (screen residue) are obtained on the sieve;
[0048] Step d, conveying the above-mentioned sieve residue to a jet mill through a pipeline, crushing it into a material with a particle size of 8 mm, screening the crushed material through a drum screen with a mesh number of 140, and separating the sieve under material into magnetic material and positive and negative electrode materials through a pipeline demagnetizer; the sieve over material is subjected to magnetic separation, gravity separation and color separation in turn to obtain magnetic material, copper powder, aluminum powder and light material; granulating the light material through a dry roller granulator 1 to obtain a copper-aluminum particle mixture;
[0049] Step e, conveying the copper-aluminum particle mixture to a linear sieve, the linear sieve is divided into two layers, the mesh number of the first layer of the sieve is 20 mesh, the mesh number of the second layer of the sieve is 200 mesh, the 20-mesh sieve is mainly a copper-aluminum particle mixture, the 200-mesh sieve is the positive and negative electrode materials, the 200-mesh sieve is mostly copper-aluminum mixed powder and a small amount of positive and negative electrode materials, conveying the 200-mesh sieve to a 200-mesh disc sieve 2 to sieve out the positive and negative electrode materials, combining the 20-mesh sieve and the 200-mesh disc sieve 2, conveying to a roller granulator 2 for granulation, and obtaining a copper-aluminum particle mixture with a particle size of 0.4 mm, and requiring its bulk density to be ≥3.8 g / cm 3 , the proportion of spherical particles is ≥80%;
[0050] Step f, conveying the copper-aluminum particle mixture to the disc sieve 3, the disc sieve 3 is divided into two layers, the mesh number of the first layer of the sieve is 25 mesh, the mesh number of the second layer of the sieve is 50 mesh, the 25-mesh sieve is organic matter, and the 50-mesh sieve is a copper-aluminum particle mixture with a particle size that meets the requirements, and the 50-mesh sieve is returned to the roller granulator 2 for circulation treatment until the particle size is qualified;
[0051] Step g, conveying the copper-aluminum particle mixture with qualified particle size to the disc screen 4 for screening, the disc screen 4 is divided into two layers, the mesh number of the first layer of the screen is 60 mesh, and the mesh number of the second layer of the screen is 100 mesh, and the copper-aluminum particle mixture is screened into 3 different particle size grades, namely 50-60 mesh, 60-100 mesh, and below 100 mesh;
[0052] Step h, conveying the copper and aluminum particle mixtures of different particle size ranges to the copper and aluminum separator for separation, and setting the air volume and vibration frequency according to the particle size, and the specific control is as follows:
[0053] Particle size 50~60 mesh, fan frequency 20Hz, vibration frequency 41Hz;
[0054] Particle size 60~100 mesh, fan frequency 18Hz, vibration frequency 38Hz;
[0055] For particle size below 100 mesh, the fan frequency is 15Hz and the vibration frequency is 35Hz;
[0056] The feeding speed is set according to the particle size of the copper-aluminum particle mixture, and the feeding speeds of the copper powder and the aluminum powder as well as the purity data of the obtained copper powder and the aluminum powder are shown in Table 1.
[0057] Table 1
[0058]
[0059] Example 2
[0060] A method for processing waste lithium-ion batteries:
[0061] Step a, placing the waste lithium-ion battery into a KCl solution with a mass concentration of 10% for discharge, so that the battery is in a power-free state;
[0062] Step b, the discharged battery is sent to the shredder through the feeder, the battery is broken into small pieces with a particle size of 20 mm, and then the battery pieces are transported to the infrared tunnel kiln through the pipeline conveyor, the infrared wavelength is adjusted to 850 μm, the temperature is increased to 400°C at a rate of 250°C / min, and the temperature is kept for 15 minutes to carbonize the binder, electrolyte, diaphragm and other organic matter;
[0063] Step c, conveying the carbonized material to a hammer crusher, the motor frequency is 35 Hz, the discharge particle size is 10 mm, and then conveying the material at the discharge port to a disc screen 1 with a mesh number of 50, the disc screen 1 has a diameter of 1.8 m, and the vibration frequency is 35 Hz, and vibrating screening is performed, and most of the positive and negative electrode materials are collected under the sieve, and the magnetic material (battery shell powder) is screened out through a pipeline demagnetizer; most of the copper-aluminum mixed powder and a small amount of organic matter, positive and negative electrode materials (screen residue) are obtained on the sieve;
[0064] Step d, conveying the above-mentioned sieve residue to a pneumatic pulverizer through a pipeline, crushing it into a material with a particle size of 10 mm, sieving the crushed material through a drum screen with a mesh number of 200, and separating the sieve under material into magnetic material and positive and negative electrode materials through a pipeline demagnetizer; the sieve over material is sequentially subjected to magnetic separation, gravity separation and color separation to obtain magnetic material, copper powder, aluminum powder and light material; granulating the light material through a dry roller granulator 1 to obtain a copper-aluminum particle mixture;
[0065] Step e, conveying the copper-aluminum particle mixture to a linear sieve, the linear sieve is divided into two layers, the mesh number of the first layer of the sieve is 10 mesh, the mesh number of the second layer of the sieve is 200 mesh, the 10-mesh sieve is mainly a copper-aluminum particle mixture, the 200-mesh sieve is the positive and negative electrode materials, the 200-mesh sieve is mostly copper-aluminum mixed powder and a small amount of positive and negative electrode materials, conveying the 200-mesh sieve to a 200-mesh disc sieve 2 to sieve out the positive and negative electrode materials, combining the 20-mesh sieve and the 200-mesh disc sieve 2, conveying to a roller granulator 2 for granulation, and obtaining a copper-aluminum particle mixture with a particle size of 0.2 mm, and requiring its bulk density to be ≥3.8 g / cm 3 , the proportion of spherical particles is ≥80%;
[0066] Step f, conveying the copper-aluminum particle mixture to the disc sieve 3, the disc sieve 3 is divided into two layers, the mesh number of the first layer of the sieve is 14 mesh, the mesh number of the second layer of the sieve is 60 mesh, the 14-mesh sieve is organic matter, and the 60-mesh sieve is a copper-aluminum particle mixture with a particle size that meets the requirements, and the 60-mesh sieve is returned to the roller granulator 2 for circulation treatment until the particle size is qualified;
[0067] Step g, conveying the copper-aluminum particle mixture with qualified particle size to the disc screen 4 for screening, the disc screen 4 is divided into two layers, the mesh number of the first stage screen is 80 mesh, the mesh number of the second stage screen is 120 mesh, and the copper-aluminum particle mixture is screened into 3 different particle size grades, namely 60-80 mesh, 80-120 mesh, and below 120 mesh;
[0068] Step h, respectively conveying the copper and aluminum particle mixtures of different particle size ranges to a copper and aluminum separator for sorting, setting the air volume and vibration frequency according to the particle size, and specifically controlling as follows: separating the magnetic substances from the sieved copper powder and aluminum powder through a pipeline demagnetizer to obtain copper powder and aluminum powder products.
[0069] Particle size 60~80 mesh, fan frequency 23Hz, vibration frequency 42Hz;
[0070] Particle size 80~120 mesh, fan frequency 19Hz, vibration frequency 37Hz;
[0071] For particle size below 120 mesh, the fan frequency is 17Hz and the vibration frequency is 35Hz;
[0072] The feeding speed is set according to the particle size of the copper-aluminum particle mixture, and the feeding speeds of the copper powder and the aluminum powder as well as the purity data of the obtained copper powder and the aluminum powder are shown in Table 2.
[0073] Table 2
[0074]
[0075] Example 3
[0076] A method for processing waste lithium-ion batteries:
[0077] Step a, placing the waste lithium-ion battery into a Na2SO4 solution with a mass concentration of 10% for discharge, so that the battery is in a power-free state;
[0078] Step b, the discharged battery is sent to the shredder through the feeder, the battery is broken into small pieces with a particle size of 150 mm, and then the battery pieces are transported to the infrared tunnel kiln through the pipeline conveyor, the infrared wavelength is adjusted to 100 μm, the temperature is increased to 600°C at a rate of 120°C / min, and the temperature is kept for 3 minutes to carbonize the binder, electrolyte, diaphragm and other organic matter;
[0079] Step c, conveying the carbonized material to a hammer crusher, the motor frequency is 45 Hz, the discharge particle size is 20 mm, and then conveying the material at the discharge port to a disc screen 1 with a mesh number of 140, the diameter of the disc screen 1 is 1.8 m, the vibration frequency is 35 Hz, and the vibration screening is performed. Most of the positive and negative electrode materials are collected under the sieve, and the magnetic material (battery shell powder) is screened out through a pipeline demagnetizer; most of the copper-aluminum mixed powder and a small amount of organic matter, positive and negative electrode materials (screen residue) are obtained on the sieve;
[0080] Step d, conveying the above-mentioned sieve residue to a pneumatic pulverizer through a pipeline, crushing it into a material with a particle size of 3 mm, sieving the crushed material through a drum screen with a mesh number of 160, and separating the sieve residue into magnetic material and positive and negative electrode materials through a pipeline demagnetizer; the sieve residue is subjected to magnetic separation, gravity separation and color separation in turn to obtain magnetic material, copper powder, aluminum powder and light material; the light material is granulated by a dry roller granulator 1 to obtain a copper-aluminum particle mixture;
[0081] Step e, conveying the copper-aluminum particle mixture to a linear sieve, the linear sieve is divided into two layers, the mesh number of the first layer of the sieve is 30 mesh, the mesh number of the second layer of the sieve is 160 mesh, the 30-mesh sieve is mainly a copper-aluminum particle mixture, the 160-mesh sieve is the positive and negative electrode materials, the 160-mesh sieve is mostly copper-aluminum mixed powder and a small amount of positive and negative electrode materials, conveying the 160-mesh sieve to a 200-mesh disc sieve 2 to sieve out the positive and negative electrode materials, combining the 30-mesh sieve and the 200-mesh disc sieve 2, conveying to a roller granulator 2 for granulation, and obtaining a copper-aluminum particle mixture with a particle size of 0.8 mm, and requiring its bulk density to be ≥3.8 g / cm 3 , the proportion of spherical particles is ≥80%;
[0082] Step f, conveying the copper-aluminum particle mixture to the disc screen 3, the disc screen 3 is divided into two layers, the mesh number of the first layer of the screen is 35 mesh, the mesh number of the second layer of the screen is 80 mesh, the 35-mesh screen is organic matter, and the 80-mesh screen is a copper-aluminum particle mixture with a particle size that meets the requirements, and the 80-mesh screen is returned to the roller granulator 2 for circulation treatment until the particle size is qualified;
[0083] Step g, conveying the copper-aluminum particle mixture with qualified particle size to the disc screen 4 for screening, the disc screen 4 is divided into two layers, the mesh number of the first stage screen is 100 mesh, the mesh number of the second stage screen is 200 mesh, and the copper-aluminum particle mixture is screened into 3 different particle size grades, namely 80-100 mesh, 100-200 mesh, and below 200 mesh;
[0084] Step h, respectively conveying the copper and aluminum particle mixtures of different particle size ranges to a copper and aluminum separator for sorting, setting the air volume and vibration frequency according to the particle size, and specifically controlling as follows: separating the magnetic substances from the sieved copper powder and aluminum powder through a pipeline demagnetizer to obtain copper powder and aluminum powder products.
[0085] Particle size 80~100 mesh, fan frequency 24Hz, vibration frequency 43Hz;
[0086] Particle size 100~200 mesh, fan frequency 22Hz, vibration frequency 38Hz;
[0087] For particle size below 200 mesh, the fan frequency is 16Hz and the vibration frequency is 31Hz;
[0088] The feeding speed is set according to the particle size of the copper-aluminum particle mixture, and the feeding speeds of the copper powder and the aluminum powder as well as the purity data of the obtained copper powder and the aluminum powder are shown in Table 3.
[0089] Table 3
[0090]
[0091] The recovery rates of copper and aluminum recovered in the above-mentioned Examples 1 to 3 can reach more than 99.5%, and the recovery rates of positive and negative electrode materials can reach more than 99.7%.
[0092] Comparative Example 1
[0093] This comparative example provides a method for treating waste lithium-ion batteries. The only difference from Example 1 is that a common programmed temperature furnace is used in step b to perform carbonization under oxygen-free vacuum conditions. Specifically, step b is as follows:
[0094] The discharged batteries are sent to the shredder through a feeder to break the batteries into small pieces with a particle size of 80 mm. The battery pieces are then transported to a programmed temperature furnace through a pipeline conveyor, heated to 500°C at a rate of 40°C / min, and kept warm for 20 minutes to carbonize the binder, electrolyte, diaphragm and other organic matter.
[0095] The remaining steps are exactly the same and will not be repeated here.
[0096] The recovery rate of copper recovered in this comparative example is 92%, the recovery rate of aluminum is 90%, the recovery rate of positive and negative electrode materials is 95%, the copper content in the separated copper powder is 91%, the aluminum content is 3%, and the organic matter content in the copper powder is 4%; the aluminum content in the aluminum powder is 87%, the copper content is 5%, and the organic matter content in the aluminum powder is 3%.
[0097] Comparative Example 2
[0098] This comparative example provides a method for treating waste lithium-ion batteries. The only difference from Example 1 is that the particle size classification in step g is not performed, and the material with qualified particle size obtained in step f is directly transported to the copper and aluminum separation for sorting. The remaining steps are exactly the same and will not be repeated here.
[0099] The recovery rate of copper recovered in this comparative example is 91%, the recovery rate of aluminum is 88%, the recovery rate of positive and negative electrode materials is 94%, and the separated copper powder has a copper content of 90%, an aluminum content of 4%, and an organic matter content of 4%; the aluminum content of the aluminum powder is 88%, a copper content of 5%, and an organic matter content of 6%.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for treating waste lithium-ion batteries, characterized in that: The following steps are involved: Step a, discharging the waste lithium-ion batteries and then shredding them to obtain battery fragments; Step b, carbonizing the battery fragments by infrared heating under oxygen-free vacuum conditions to obtain carbonized battery fragments; Step c, placing the carbonized battery fragments in a stripping device provided with a rotary extrusion structure for stripping, and screening the obtained material through a first sieve to obtain a positive and negative electrode mixed powder and a primary sieve residue; Step d, the first-level sieve residue is subjected to air flow pulverization and then sieved through a second sieve to obtain positive and negative electrode mixed powder and a second-level sieve residue; the second-level sieve residue is subjected to magnetic separation, gravity separation and color separation in sequence to obtain magnetic material, copper particles, aluminum particles and light materials respectively; the light materials are roller-granulated and then subjected to three-level screening to obtain positive and negative electrode mixed powder and copper-aluminum mixed powder; the copper-aluminum mixed powder is roller-granulated to obtain a copper-aluminum particle mixture; The three-stage screening specifically includes the following steps: screening the material after roller granulation through linear sieves with mesh numbers of 10-30 mesh and 140-200 mesh in turn, collecting the copper-aluminum mixed powder on the 10-30 mesh linear sieve, and collecting the positive and negative electrode mixed powder under the 140-200 mesh linear sieve; The material on the 140-200 mesh sieve is sieved through a 140-200 mesh disc sieve, and the copper-aluminum mixed powder is collected on the sieve, and the positive and negative electrode mixed powder is collected under the sieve; The copper-aluminum mixed powders are combined and granulated by roller pressing to obtain a copper-aluminum particle mixture; Step e, screening the copper-aluminum particle mixture through a 14-40 mesh disc sieve, collecting organic matter on the 14-40 mesh sieve, and then screening the copper-aluminum particle mixture without organic matter through a third sieve, collecting the material under the sieve, and screening the material under the sieve through a fourth sieve and a fifth sieve in sequence to obtain a copper-aluminum particle mixture with three particle size specifications; returning the copper-aluminum particle mixture on the third sieve to roller granulation and continue with subsequent steps; The mesh number of the fifth sieve is greater than the mesh number of the fourth sieve and greater than the mesh number of the third sieve. The mesh number of the third sieve is 50-80 meshes, the mesh number of the fourth sieve is 60-100 meshes, and the mesh number of the fifth sieve is 80-200 meshes. Step f, transporting the copper and aluminum particle mixtures of different particle sizes to the copper and aluminum separation system for separation to obtain copper particles and aluminum particles.
2. The method for treating waste lithium-ion batteries according to claim 1, characterized in that: In step a, the waste lithium-ion battery is discharged in a salt solution with a mass concentration of 1% to 20%; and / or In step a, the particle size of the battery fragments is 20 mm to 150 mm.
3. The method for treating waste lithium-ion batteries according to claim 1, characterized in that: In step b, the temperature of the infrared heating carbonization is 400°C to 600°C, the heating rate is 100°C / min to 300°C / min, the insulation time is 3min to 15min, and the infrared wavelength is 0.75μm to 1000μm.
4. The method for treating waste lithium-ion batteries according to claim 1, characterized in that: In step c, the stripping device is a hammer crusher.
5. The method for treating waste lithium-ion batteries according to claim 1, characterized in that: In step c, the frequency of the stripping device is 35 Hz to 45 Hz, and the particle size of the output material is 10 mm to 20 mm; and / or In step c, the mesh size of the first sieve is 50 mesh to 140 mesh.
6. The method for treating waste lithium-ion batteries according to claim 1, characterized in that: In step d, the particle size of the material after air flow pulverization is 1 mm to 10 mm; and / or In step d, the second screen is a drum screen, and the mesh number of the drum screen is 140 mesh to 200 mesh.
7. The method for treating waste lithium-ion batteries according to claim 1, characterized in that: In step d, the particle size of the copper-aluminum particle mixture is 0.2 mm to 0.8 mm, and the bulk density is ≥ 3.8 g / cm 3 , the proportion of spherical particles is ≥80%.
8. The method for treating waste lithium-ion batteries according to claim 1, characterized in that: In step f, the air volume and vibration frequency are set according to the particle size of the copper-aluminum particle mixture, wherein the particle size of the copper-aluminum particle mixture is 60-100 mesh sieve, the fan frequency is 10Hz-35Hz, and the vibration frequency is 41Hz-48Hz; the particle size of the copper-aluminum mixture is 80-200 mesh sieve, the fan frequency is 10Hz-35Hz, and the vibration frequency is 35Hz-40Hz; the particle size of the copper-aluminum mixture is 80-200 mesh sieve, the fan frequency is 10Hz-35Hz, and the vibration frequency is 31Hz-35Hz.
Citation Information
Patent Citations
Waste lithium ion battery recycling method
CN107946686A
Method for recycling copper aluminum and rubber in waste power lithium battery
CN109378542A